Digital hunters - Ramakrishnan, Prabha (Universiti Teknologi MARA, Sarawak, 2004)
This article focuses on the modern jungle where tall trees are called skyscrapers and the multicolored roots of the trees are known as computer network cables. In these jungles live the digital hunters. They capture and bring home massive catch of knowledge using vast high-speed nets. The UiTM Kota Samarahan's Local Area Network (LAN) within the campus is such a net for all knowledge-hunters here. Composed of leading-edge computer networking devices and the finest cables, the UiTM's network configuration is as good as or better than the multitude of LANs across Sarawak.